Orchid bee fauna responds to habitat complexity on a savanna area (Cerrado) in Brazil. - Antonini, Yasmine; Silveira, Rodrigo Assunção; Oliveira, Márcio; Martins, Cristiane; Oliveira, Reisla (Sociobiology, 2016)
Habitat structure and complexity may broadly affect the diversity and composition of a variety of fauna in terrestrial systems. Here we investigated responses of orchid bee assemblages to habitat complexity, with the aim of assessing complexity as a useful surrogate for species diversity of this group. We test the following hypotheses: (i) There is a greater species richness and abundance of orchid bee in sites with high habitat complexity than lower habitat complexity; (ii) High habitat complexity sites have a different species composition of orchid bee than lower habitat complexity sites. For the purposes of our study, we defined habitat complexity as the heterogeneity in the arrangement in physical structure of habitat (vegetation), although there are a large range of operational definitions in the literature. As result, orchid bee species richness was higher in high complexity areas while community composition was not affected by habitat complexity, because Euglossa melanotricha and E. leucotricha were the dominant species, occurring in both environments. Habitat complexity, measured as a function of differences in multiple strata in forests, may be of great worth as a surrogate for the diversity of a range of arthropod groups including orchid bees.